Sepak Takraw Playing Skills of SMANOR Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of sepak takraw playing skills among athletes at SMANOR Tadulako, Central Sulawesi. A descriptive quantitative approach was employed, using total sampling techniques involving all 36 sepak takraw athletes. The data collection instrument consisted of a skill test covering six aspects: service (start kick), inside kick (sila kick), horse kick (horse kick), heading, smash, and thigh control (thigh). The results showed that the majority of athletes were in the "moderate" category across almost all skill aspects. In the service test, 44.44% of athletes were classified as moderate, inside kick 41.67%; horse kick 36.11%; headings 44.44%; smash 38.89%; and thigh control 41.67%. These findings indicate that the athletes' mastery of both basic and specific techniques has not yet reached an optimal level. It is concluded that the overall sepak takraw playing skills of SMANOR Tadulako athletes remain at a moderate level, thus requiring more intensive technical coaching, varied training methods, and regular evaluations to improve athletes' performance comprehensively.